The Effect of Parenting Styles Using Athoritarian Methods on the Independence of 7-Year-Old Children during the Covid 19 Pandemic - Suryani, Iis Sopiah; Nurakilah, Heni; Daryanti, Eneng; Jamil, Maria Ulfah; Sulastri, Meti; Marlina, Lina; Amalia, Novianti Rizki (Indonesian Operations Research Association (IORA), 2023)
The Indonesian government has made policies in almost all fields. That is to prevent the spread of the Covid-19 virus, with one of them being the policy of workers to work from home and study from home which is often also called online or online learning. Early childhood education to tertiary institutions practice online learning policies so that children are at home for 24 hours. During the pandemic, children were accompanied by their parents studying at home online. Thus, parents must have the right parenting style in accompanying children while at home. Good behavior emerges from good parenting. To produce independence for children during a pandemic, they must also apply good parenting. state the problem One effective way to increase independence is to provide good parenting. purpose of your study to determine the effect of anoritarian parenting on the independence of children aged 7 years describe the research methods; the method used is by means of analytic observation tested using chi suare. results or outcomes of the work parenting style with authoritarian methods has an effect even if only partially on the independence of children aged 7 years. This research can make it easier for parents to educate their children in self-sufficient children, especially during the postcovid 19 pandemic. the method used is by means of analytic observation tested using chi suare. results or outcomes of the work parenting style with authoritarian methods has an effect even if only partially on the independence of children aged 7 years. This research can make it easier for parents to educate their children in self-sufficient children, especially during the post-covid 19 pandemic. the method used is by means of analytic observation tested using chi suare. results or outcomes of the work parenting style with authoritarian methods has an effect even if only partially on the independence of children aged 7 years. This research can make it easier for parents to educate their children in self-sufficient children, especially during the post-covid 19 pandemic.